Cardiac mTORC1 Dysregulation Impacts Stress Adaptation and Survival in Huntington’s Disease - Child, Daniel D. (Cell Rep, 2018)
Huntington’s disease (HD) is a dominantly inherited neurological disorder caused by CAG-repeat expansion in exon 1 of Huntingtin (HTT). But in addition to the neurological disease, mutant HTT (mHTT), which is ubiquitously expressed, impairs other organ systems. Indeed, epidemiological and animal model studies suggest higher incidence of and mortality from heart disease in HD. Here, we show that the protein complex mTORC1 is dysregulated in two HD mouse models through a mechanism that requires intrinsic mHTT expression. Moreover, restoring cardiac mTORC1 activity with constitutively active Rheb prevents mortality and relieves the mHTT-induced block to hypertrophic adaptation to cardiac stress. Finally, we show that chronic mTORC1 dysregulation is due in part to mislocalization of endogenous Rheb. These data provide insight into the increased cardiac-related mortality of HD patients, with cardiac mHTT expression inhibiting mTORC1 activity, limiting heart growth, and decreasing the heart’s ability to compensate to chronic stress.